Government and farmer responses to the fall armyworm outbreak in mainland Southeast Asia - Kusano, Eiichi; Poapongsakorn, Nipon; Jantarasiri, Urairat; Pantakua, Kamphol; Tran, Cuong H.; Khin Akari Tar,; Kong, Thong; Phimphachanhvongsod, Viengsavanh V.; Kobori, Youichi (Frontiers in Insect Science, 2025)
IntroductionNative to the Americas and highly polyphagous, the fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) has garnered attention for causing significant damage, primarily to maize.MethodsThis study synthesizes FAW emergence, government responses, and farmer reactions in mainland Southeast Asia (MSEA), and assesses the feasibility of government-recommended measures in terms of efficacy and cost-efficiency.ResultsFrom late 2018 to the rainy season of 2019, FAW infestations extensively emerged in MSEA maize fields. MSEA governments promptly issued strategies and guidelines through plant protection divisions/departments, which involved international organizations, foreign governments, and private web portals. Alongside the foliar application of emamectin benzoate (EMB), which is the most frequently mentioned method, MSEA governments advocated for integrated pest management (IPM)-oriented approaches. These include application methods of chemical insecticides, use of host plant resistance, biological control, cultural and interference methods, and local measures aimed at reducing chemical usage. Despite comprehensive recommendations, maize farmers primarily rely on EMB foliar treatment for FAW control.DiscussionWe highlight the need for further research and dissemination regarding the widely accepted foliar application of chemical insecticides, specifically in relation to human safety, improvements in application technology, and clear guidelines for large-scale outbreaks. On the other hand, the concentrative foliar application of chemical insecticides raises concerns about resistance evolution. Alternatives to foliar treatment with chemical insecticides, mainly EMB, such as seed treatment with diamides and neonicotinoids, genetically modified maize seeds approved only in Vietnam, and biological control, have demonstrated efficacy. Seed treatment provides cost and labor benefits for early-stage FAW infestation prevention. Validation of natural enemy rearing costs may prove advantageous as preliminary estimates suggest they could be relatively low. Not all strategies recommended by the government or widely discussed are necessarily relevant at farm-level. This study provides the following suggestions for the proposal of more acceptable strategies. 1) Studying the actual responses of governments and farmers with special emphasis on cost efficiency; 2) Making alternatives to EMB foliar application more cost-effective inclusive of the cost of labor; and finally, 3) Verifying the effectiveness of the alternative techniques.